2019
DOI: 10.1108/md-11-2017-1139
|View full text |Cite
|
Sign up to set email alerts
|

Intangibles and performance in oil and gas industry

Abstract: Purpose The purpose of this paper is to assess the extent to which financial and market performance of companies in the oil and gas sector can be attributed to the value of their intangibles. Design/methodology/approach The research utilized publicly available data on global oil and gas companies from 2000 to 2015. Panel data analysis was used to assess the relationship between intangibles (measured by Calculated Intangible Value (CIV)) and financial and market performance of these companies. Findings Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 62 publications
0
11
0
3
Order By: Relevance
“…For the last several decades, business firms across the globe have been competing for Sustainable Competitive Advantage (SCA) and sustainable growth (SG; Lee & Lee, 2019;Maury, 2018;Xu & Wang, 2018). Some firms invest in intangible resources such as machinery (Shirodkar & Mohr, 2015), land and equipment (Mitra et al, 2016), and technology (Khallaf et al, 2017), whereas other firms prefer investment in intangible resources such as Intellectual Capital (IC), Corporate Social Responsibility (CSR; Sampong et al, 2018), knowledge (Dženopoljac et al, 2019;Ying et al, 2019), and entrepreneurial activities (Kiyabo & Isaga, 2020). In other words, previous studies have suggested several determinants that can spur firms' SCA and SG (Lee & Lee, 2019;Maury, 2018;Xu & Wang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For the last several decades, business firms across the globe have been competing for Sustainable Competitive Advantage (SCA) and sustainable growth (SG; Lee & Lee, 2019;Maury, 2018;Xu & Wang, 2018). Some firms invest in intangible resources such as machinery (Shirodkar & Mohr, 2015), land and equipment (Mitra et al, 2016), and technology (Khallaf et al, 2017), whereas other firms prefer investment in intangible resources such as Intellectual Capital (IC), Corporate Social Responsibility (CSR; Sampong et al, 2018), knowledge (Dženopoljac et al, 2019;Ying et al, 2019), and entrepreneurial activities (Kiyabo & Isaga, 2020). In other words, previous studies have suggested several determinants that can spur firms' SCA and SG (Lee & Lee, 2019;Maury, 2018;Xu & Wang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, non-financial performance is defined as the intangible performance that an organization (Dženopoljac et al, 2019;Molodchik et al, 2019;Zigan and Zeglat, 2010) has obtained over its competitors in the market, in terms of quality, cost advantage, timely delivery, sales volume and market share (Hoque and James, 2000;Mia and Clarke, 1999;Noordin et al, 2015). Based on the above, the following hypothesis is established:…”
Section: Tangible and Intangible Resultsmentioning
confidence: 99%
“…This makes it more user‐friendly. Therefore, academic researchers in this field tend to use VAIC more often, and only a few research studies have successfully applied CIV (e.g., Dzenopoljac et al, 2019; Kennedy, 1998; McClure, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, one certainty is the uncertainty of investments in intangibles. Although few studies included time as the factor of the IC‐performance relationship (Dzenopoljac et al, 2019), many companies realize the existence of a significant time lag between IC investments and their positive (or negative) effect on company performance. Moreover, IC performance is perceived to be “distant” from financial performance as that the succession of events and the time lags are difficult to define and quantify.…”
Section: Literature Reviewmentioning
confidence: 99%